IF THE QUESTION OF REPETITION WERE TO ARISE OTHERWISE? - Jacques Balthasar GEORGES (Universitaria Publishing House, Craiova, 2023)
Repetition, at the heart of many discussions between education professionals, now appears useful to some, useless to others. He questions the organization of activities for some, he presents himself as an enemy to be defeated for others. But do not the consonants and dissonants that appear following the disputes, through papers, between pedagogues and sociologists of education disturb the tranquility necessary for the understanding of this phenomenon? The exploratory study presented below attempts, modestly, to highlight some elements beneficial to a new problematization of this particular phenomenon.